Birth preparedness and complication readiness for a safe motherhood among antenatal women attending an urban health centre, Pudupet - Vidhyashree, M. D.; S., Janani; P., Kavipriya; V., Lakshmi; S., Sindhukavi; K., Suganya (International Journal Of Community Medicine And Public Health, 2020)
Background: Maternal and neonatal mortality is a significant medical issue in creating nations. Birth preparedness and complication readiness (BPCR) is a technique to urge pregnant ladies to settle on brief choices to look for care from talented birth orderlies. Most investigations of BPCR have been led in creating nations, BPCR status and related factors in Pudupet are at present obscure. Objectives were to evaluate BPCR for a sheltered parenthood among antenatal (AN) moms going to an urban health center, Pudupet and to recognize the factors affecting BPCR. Methods: The examination was directed among 104 pregnant women in a community based cross sectional study conducted in urban health training centre (UHTC) was conducted among 104 pregnant women as per inclusion criteria by simple random sampling. A predesigned semi structured questionnaire by interview method after taking informed consent was used to calculate socio demographic details and antenatal care. Data were entered and analysed in Epi-info software. Results: Overall BPCR score was 96.15% of women scored 3 and above. But awareness about blood donor (13.5%) was less among antenatal mothers. Money savings either cash or insurance was kept ready by 49 (47.1%). Articles kept ready by 42 (40.4%) AN mothers. Among 104, 71(68.3%) had awareness over birth control measures. Significance seen under statistical analysis among sociodemographic factors like age, education, socioeconomic status, husband’s education and type of family had statistically significant associations with BPCR components. Conclusions: Birth preparedness and difficulty status is fundamental and viable methodology that supports mother, family and network to design a protected conveyance.